PENDAMPINGAN MENULIS PANTUN SEBAGAI AKAR LITERASI SISWA KELAS VB DI UPT SPF SD NEGERI BADDOKA KOTA MAKASSAR - Rahma Ashari Hamzah; Nurhayati Selvi; Wahyullah Alannasir (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
The purpose of implementing community service is regarding assisting in writing rhymes as the root of student literacy, the goal is to provide knowledge and understanding to students in terms of writing rhymes. Activities carried out in mentoring activities for writing rhymes as the root of student literacy begin with introductions by the chairman and members of community service activities with fifth B grade students at UPT SPF SD Negeri Baddoka Makassar City, where the number of participants is 29 students. The next activity is the chairman of the activity explaining material regarding the explanation of the rhymes themselves, an explanation of the characteristics of the rhymes, an explanation of the types of rhymes, and an explanation of examples of rhymes according to their types such as advice rhymes, humorous rhymes, religious rhymes, and so on. After mentoring, the results obtained are that students know the meaning of the rhymes themselves, students can write rhymes according to the characteristics of the rhymes themselves, students are creative in making rhymes according to the type they want, and students can think of which lyrics are appropriate to use in producing rhymes that both as the root of student literacy as evidenced by the rhymes written by students.